Maturation rate of sheep oocytes cultured in suboptimal environment using CO2 exhaled by human and glutathione addition - S. Prastowo; R. Widyastuti (Journal of the Indonesian Tropical Animal Agriculture, 2022)
This study aimed to identify the effect of the use of CO2 exhaled by human (CEbH) in in vitro maturation (IVM) with the addition of Glutathione also known as GSH on the oocytes maturation rate. It is known that CO2 derived from human respiration can be used as alternative support for IVM of oo-cytes. However, this method is categorized as using a suboptimal culture environment, and it results in increased production of reactive oxidative species (ROS). Thus, the addition of the antioxidant GSH is needed. In total, 273 oocytes were cultured in three groups: 5% CO2 (control) and CEbH with 0 mM and 1 mM of GSH addition, respectively. The results showed that the control group produced a better maturation rate (p < 0.05) compared to the remaining two groups (65.92% vs. 24.44% and 30.61%), which used CEbH. Statistically, 0 mM GSH vs. 1 mM GSH did not show any significant differences (p > 0.05). However, 1 mM GSH led to more mature oocytes (24.44% vs 30.61%) compared to the group without GSH. In conclusion, IVM using CEbH supports oocyte maturation, and the addition of GSH can improve the maturation rate in a suboptimal culture environment.